Silver Nanoparticles Coated with Recombinant Human Epidermal Growth Factor: Synthesis, Characterization, Liberation and Anti-Escherichia coli Activity - Gonzales Matushita, Layla M. (2023)
Epithelial tissue regeneration may be favored if the tissue receives both therapeutic agents such as recombinant human epidermal growth factor (rhEGF) and, simultaneously, antibacterial materials capable of reducing the risk of infections. Herein, we synthesized silver nanoparticles (AgNPs), which are well-known antibacterial materials, and impregnate them with rhEGF in order to study a bio-nanomaterial of potential interest for epithelial tissue regeneration. A suspension of Ag NPs is prepared by the chemical reduction method, employing sodium citrate as both a reducer and capping agent. The AgNPs suspension is mixed with a saline solution containing rhEGF, producing rhEGF-coated Ag NPs with rhEGF loadings between 0.1 and 0.4% w/w. ELISA assays of supernatants demonstrate that, in all studied cases, over 90% of the added rhEGF forms part of the coating, evidencing a high efficiency in impregnation. During the preparation of rhEGF-coated Ag NPs, no significant changes are observed on the nanoparticles, which are characterized by UV-Vis spectroscopy, transmission electron microscopy (TEM) and infrared spectroscopy. The liberation of rhEGF in vitro was followed for 72 h, finding that approximately 1% of rhEGF that is present is released. The rhEGF-coated AgNPs shows antibacterial activity against E. coli, although such activity is decreased with respect to that observed from naked AgNPs. Having confirmed the possibility of simultaneously liberating rhEGF and reducing the proliferation of bacteria, this work helps to support the use of rhEGF-loaded metallic nanoparticles for tissue regeneration.